The European pillar of social rights: critical legal analysis and proposals - Lörcher, Klaus; Schömann, Isabelle (Brussels, 2016)
"The aim of the present paper is to provide a basis for an in-depth discussion of the European Commission’s initiative for a ‘European Pillar of Social Rights’ by briefly examining its context. The content of the Commission’s Communication is reviewed and followed by a more detailed analysis of the rights listed in the Annex of the Communication."